2020
DOI: 10.1038/s41598-020-68839-w
|View full text |Cite
|
Sign up to set email alerts
|

Early evidence of fire in south-western Europe: the Acheulean site of Gruta da Aroeira (Torres Novas, Portugal)

Abstract: the site of Gruta da Aroeira (torres novas, portugal), with evidence of human occupancy dating to ca. 400 ka (Marine Isotope Stage 11), is one of the very few Middle Pleistocene localities to have provided a fossil hominin cranium associated with Acheulean bifaces in a cave context. the multianalytic study reported here of the by-products of burning recorded in layer X suggests the presence of anthropogenic fires at the site, among the oldest such evidence in southwestern Europe. The burnt material consists of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 69 publications
0
11
0
3
Order By: Relevance
“…Dazzling and bewilderment could be promoted by the light of torches or even through controlled fires with parapets of branches at the entrance to the cavities, both also producing heat, noise and smoke increasing confusion in the choughs. In fact, Neanderthals mastered the use of fire all along their existence as a species from about 400-300,000 years ago (Roebroeks and Villa, 2011;Sanz et al, 2020;MacDonald et al, 2021), and the use of constructions inside of long caves in total absence of natural light also testifies of the use of fire for illumination (Jaubert et al, 2016). This would support Neanderthal use of fire for hunting and, to our knowledge, this is the first documented suggestion of social hunting of birds at night with the help of fire technology.…”
Section: Discussionmentioning
confidence: 99%
“…Dazzling and bewilderment could be promoted by the light of torches or even through controlled fires with parapets of branches at the entrance to the cavities, both also producing heat, noise and smoke increasing confusion in the choughs. In fact, Neanderthals mastered the use of fire all along their existence as a species from about 400-300,000 years ago (Roebroeks and Villa, 2011;Sanz et al, 2020;MacDonald et al, 2021), and the use of constructions inside of long caves in total absence of natural light also testifies of the use of fire for illumination (Jaubert et al, 2016). This would support Neanderthal use of fire for hunting and, to our knowledge, this is the first documented suggestion of social hunting of birds at night with the help of fire technology.…”
Section: Discussionmentioning
confidence: 99%
“…Bone tools only rarely survive, but dispersed evidence reflects widespread use (Brühl, 2003;Julien et al, 2015;van Kolfschoten et al, 2015;Moigne et al, 2016;Zutovski and Barkai, 2016). Alongside these developments we see better evidence for fireuse from MIS 11 at Beeches Pit (UK), Terra Amata (France) and Gruta da Aroeira (Portugal), together with MDI (Gowlett et al 2005;Roebroeks and Villa, 2011;de Lumley et al, 2015;Sanz et al, 2020).…”
Section: In the Context Of Late Middle Pleistocene Europementioning
confidence: 95%
“…Studies published following this review have strengthened this pattern and identified its existence beyond Europe. In the Gruta da Aroeira cave site (Portugal), for example, fire proxies in the form of heated bones start to appear in layers dated to 400 ka ( 29 ). At Bolomor Cave (Spain), 14 hearths associated with heated materials have been excavated from multiple levels dating from 350 to 100 ka ( 30 ).…”
Section: The Spatiotemporal Pattern Of Fire Usementioning
confidence: 99%
“…However, the anthropogenic status of most of the pre–400-ka traces remains controversial (see, e.g., refs. 19 , 29 and 59 – 62 ): as an example, the origin of 1.5-Ma-old reddened patches of sediments at the FxJj20, Koobi Fora, Kenya, has been debated from initial publication four decades ago to the present day ( 56 , 57 , 59 , 63 , 64 ). An in-depth review of the pre–400-ka evidence is beyond the remit of our paper, but the record from several distinctive landscapes illustrates the isolated and problematic nature of the early fire record.…”
Section: The Spatiotemporal Pattern Of Fire Usementioning
confidence: 99%